Lithuanian Population After the Socio-Economic Transition - Stanaitis, Algirdas (Bulletin of Geography. Socio-economic Series, 2010)
The article presents changes of Lithuanian population after the restoration of state self-dependence and future prognoses. The article is based on the data at the Statistical Department of the Republic of Lithuania. There are brief analysis of the principal demographic indices: natural movement of population and migration flows. The analysis embraces the years before and after restoration of independence and future perspectives. The results of analysis was showed that the negative natural increment and migration balance have adversely affected other demographic indices: age structure, lifespan, number of marriages, deaths due to external causes, etc.